Reducing Pain Score using Finger Hold Technique on Patient with Mild Head Injury in Emergency Department (of) General Hospital Brigadier H Hasan Basry Kandangan 2018 - Rahman, Budiya; Khalilati, Noor (Journal Of Nursing Practice, 2019)
Background: Treatment for patients who have mild head injury are mostly pharmacological. (Despite of what happens to the patients so far, they do not have to be given drugs as treatment, they can be treated in other ways, that is not in the form of drugs) Purpose: To determine effect of the finger hold technique on decreasing the scale of acute pain on patients with mild head injury. Method: This research used Quasy Experimental design with the One Group Pretest-Postest Design. The population of Mild Head Injury patients in the first semester of 2018 in November-December were 20 people. Samples taken by Accidental Sampling technique in 20 respondents. Instrument for this reseach used the questionnaire sheet. Measurement of respondent's pain level using NRS rating scale 0-10 and the data analyzed using univariate analysis and bivariate analysis with Paired T-Test. Results: The scale of pain before the finger hold technique on mild head injury patients mostly got moderate pain on 15 people (75%). The scale of pain after the finger hold technique was performed, head injury patients mostly got mild pain category on 13 people (65%). The hypothesis is accepted with a significance level of 0.000 <0.05. Conclusion: By giving finger hold technique, it can decrease pain level patients with mild head injury